2022
DOI: 10.1111/dar.13502
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccination coverage and vaccine hesitancy among people with opioid use disorder in Barcelona, Spain

Abstract: Introduction People with substance use disorders are considered a priority group for SARS‐CoV‐2 vaccination as they are at elevated risk of COVID‐19 and its severe complications. However, data are scarce about vaccination coverage in a real‐world setting. Methods A descriptive study was conducted in people with opioid use disorder (OUD) from three public centres for outpatient drug addiction treatment in Barcelona, Spain, who received brief medical advice and were refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…However, the percentage of PWUD who received dose 2 is still on level with the total Norwegian population (19). In contrast, several studies have found a lower cumulative vaccine uptake mong PWUD compared to the general population (51)(52)(53)(54)(55)(56). Some studies suggest that this can be explained by hesitancy towards the vaccines among PWUD (52,54).…”
Section: Discussionmentioning
confidence: 97%
“…However, the percentage of PWUD who received dose 2 is still on level with the total Norwegian population (19). In contrast, several studies have found a lower cumulative vaccine uptake mong PWUD compared to the general population (51)(52)(53)(54)(55)(56). Some studies suggest that this can be explained by hesitancy towards the vaccines among PWUD (52,54).…”
Section: Discussionmentioning
confidence: 97%
“…Given the higher COVID-19 complications in OUD cases, preventive measures such as vaccination should be especially considered in them in order to reduce the COVID-19 burden in this highly susceptible population. This is of more importance as there has been a report that complacency and convenience were the main barriers to COVID-19 vaccination in people with OUD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few participants also reported inconvenience as a reason for not getting the vaccine; among vaccine-motivated persons with OUD, low perceived risk of COVID-19 and inconvenience (e.g. geographical difficulties to access, visiting centre schedule) have been found to be the main barriers to vaccination [ 46 ]. Reducing barriers to care by providing rideshare vouchers and efforts to overcome vaccine misinformation to increase vaccination rates should be prioritized.…”
Section: Discussionmentioning
confidence: 99%